ETHNO IPS: INOVASI MATERI PEMBELAJARAN IPS BERBANTUAN UNSUR BUDAYA - Zahid Zufar At Thaariq; Rista Anggraini; Surrotul Hasanah (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
The purpose of this study is to review an innovation of social science (IPS) learning material that uses cultural elements. Innovation in learning is useful as a tool used for learning. Therefore, in the field of learning, teachers creativity, especially in the IPS was very important. In this case, the author offers learning IPS used cultural elements of Ethno IPS. Ethno IPS is a merger of social sciences such as sociology, geography, economics and history with cultural elements. Hopefully, this implementation can increase the knowledge of cultural diversity in Indonesia and as a reference to learning and teaching more interesting.